PENGARUH PENDEKATAN SAINTIFIK DAN PARTISIPASI SISWA TERHADAP KEAKTIFAN BELAJAR SISWA KELAS X BISNIS DARING DAN PEMASARAN PADA MATA PELAJARAN DASAR-DASAR PEMASARAN DI SMK NEGERI 13 MEDAN - Serina Betsella Br Tarigan; Randeska Manullang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The level of learning activeness among Grade X students in the Online Business and Marketing program at SMK Negeri 13 Medan in the subject of Marketing Fundamentals is still conventional and passive, characterized by lecture-dominated teaching and minimal active student participation during the learning process. Therefore, it is necessary to implement a more varied model that can enhance students' learning activeness more effectively. This study aims to determine the influence of the scientific approach on the learning activeness of Grade X students in Online Business and Marketing at SMK Negeri 13 Medan.The sample used in this study consisted of 36 students, with a one-group pretest-posttest research design. Based on the paired samples t-test data analysis, the significance value (Sig) was 0.000 and the t-count was 11.717. These results show that the significance value of 0.000 < 0.05 and the t-count of 11.717 > 1.690, thus it can be concluded that the first hypothesis is accepted. This means there is a significant difference resulting from the implementation of the Scientific Approach on students' learning activeness in the Marketing Fundamentals subject for Grade X Online Business and Marketing students at SMK Negeri 13 Medan. The difference in scores between the pretest and posttest was 17.22.From the Coefficientsa test results, the variable of Student Participation (X2) obtained a significance value of 0.000 and a t-count of 4.845. This indicates that Sig = 0.000 < 0.05 and t-count > t-table (4.845 > 1.690). Therefore, hypothesis H2 is accepted, and it can be concluded that Student Participation (X2) partially has a positive and significant effect on Learning Activeness (Y) of Grade X Online Business and Marketing students at SMK Negeri 13 Medan. Based on the table, the R² value is 0.408. This means that the influence of Student Participation (X2) on the variable of Learning Activeness in the Marketing Fundamentals subject for Grade X students in the Online Business and Marketing program at SMK Negeri 13 Medan is 40.8%.